A label-free electrochemical immunosensor with a novel signal production and amplification strategy based on three-dimensional pine-like Au–Cu nanodendrites. Issue 40 (7th May 2015) - Wang, Yulan; Li, Yueyun; Ma, Hongmin; Ren, Xiang; Cao, Wei; Yan, Tao; Wei, Qin
<x xml:space="preserve">Abstract</x> A simple and novel label-free electrochemical immunosensor based on a bimetallic alloy was fabricated in this work.